PRINCIPLE OF EXTENSION OF THE MORTGAGE FOR THE CONSTRUCTION AND SEPARATE PARTS OF THE IMMOVABLE PROPERTY UNDER CONSTRUCTION - Jotanović, Radenko; Čubrilović Stamenić, Bosiljka (Glasnik Advokatske komore Vojvodine, 2023)
According to the principle of legal unity of immovable property, immovable property is a parcel of land and everything permanently attached to it on or below the surface. The reform of the real-legal system in the Republic of Srpska established the legal unity of immovable property between land, building, and separate parts of immovable property so that the owners of separate parts of immovable property become (co)owners of the entire immovable property (land and building). Immovable property, which is identified with land, is the object of property rights and the object of a mortgage. Following the principle of extensivity, the mortgage concerns the property as a whole, which means that the mortgage on the land comprises the building and a separate part of the property (apartment, commercial premises, garage, etc.). The acquisition of ownership rights and the acquisition of a mortgage on real estate as a whole is possible based on the principle of trust, which has priority over the principle of Nemo plus iuris ad alium transferre potest quam ipse habet. Concerning buildings and separate parts of buildings under construction, the application of the principle of extensivity of the mortgage or the principle of dependency depends on the moment of acquisition of the right of ownership or the mortgage. The principle of the extensiveness of the mortgage has priority if the owner of the land obtained registration of the mortgage before the sale of the building, that is, a separate part of the real estate under construction, and vice versa, the principle of trust has priority if the conscientious buyer of a separate part of the property under construction obtained registration before the constitution of the mortgage on the land.